O25-1 Pesticide use and thyroid cancer incidence among spouses of pesticide applicators in the agricultural health study. (1st September 2016) - Lerro, Catherine; Freeman, Laura Beane; Koutros, Stella; Andreotti, Gabriella; Hofmann, Jonathan; DellaValle, Curt; Alavanja, Michael; Sandler, Dale; Chen, Honglei; Blair, Aaron; Ward, Mary
Abstract : Background: Increasing thyroid cancer incidence in the US and other western countries suggests a role for environmental risk factors. There are few established risk factors for thyroid cancer, aside from ionising radiation exposure. Thyroid hormone disrupting chemicals, such as certain pesticides, have garnered interest as potential risk factors. We evaluated personal use of specific pesticides and thyroid cancer incidence among female spouses of pesticide applicators in the prospective Agricultural Health Study (AHS) cohort. Methods: At enrollment (1993–1997) spouses provided information about ever use pesticide active ingredients and additional covariates. For 12 pesticides with ≥5 exposed cases we used multivariate Poisson regression to estimate relative risks (RRs) and 95% confidence intervals (95% CIs) for incident thyroid cancers diagnosed from enrollment through 2012 (North Carolina)/2013 (Iowa), adjusted for confounders. Results: Among 31, 055 female spouses, 56% reported any personal use of pesticides. A total of 104 thyroid cancer cases were diagnosed during follow-up. Spouses who reported ever applying dicamba were at significantly increased risk of thyroid cancer (RR = 2.34, 95% CI: 1.03–5.35). Atrazine (RR = 2.00, 95% CI: 0.88–4.57) and metolachlor (RR = 2.22, 95% CI: 0.92–5.35) were associated with non-significantly elevated thyroid cancer risk, and carbaryl was associated with non-significantly decreased risk (RR = 0.61, 95% CI: 0.36–1.03). Conclusions: Our findings suggest that personal use of specific pesticides (dicamba, atrazine, and metolachlor) may be associated with thyroid cancer risk among female spouses of pesticide applicators. We noted a significant positive association with dicamba, an herbicide previously associated with self-reported hypothyroidism among male pesticide applicators in the AHS. The potential association with atrazine, a suspected endocrine disrupting chemical, is consistent with the previously observed increased risk of thyroid cancer among male pesticide applicators who apply atrazine. This study represents the first comprehensive prospective analysis of specific pesticide active ingredients and thyroid cancer risk among women; as such, our findings warrant further evaluation.